A Survey Study: The Students’ Reticence in English Classroom at Senior High School in Pekanbaru - rizki gushendra; dinda suci aprianti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The students are expected to be active in teaching and learning process. However, according to the preliminary study on Senior High in Pekanbaru. The students still have problem in learning English. They are reticent and passive in the classroom. They tend to be silent and quiet during the learning process. The class participation is far from the expectation of the learning objective from the curriculum. Therefore, this research was aimed to find out the factors that influenced students’ reticence in English classroom and the dominant factor that caused students reticence at Senior High School in Pekanbaru. This research is descriptive quantitative research, which data were collected by a questionnaire. The sample was randomly selected for 102 students out of 289 students of population. the writer found the factors that influence of students’ reticence in English classroom; First, they are the individual factors with 3.05 mean score by the percentage was 61.1%. Second, psychological factors with 2.71 mean score by percentage 54.3%. Third, affective factors with 2.65 mean score by percentage 53%. Fourth, environment factors with 2.60 mean score by percentage 52.1%. Finally, linguistic factors with 2.53 mean score by 50.6%. Meanwhile, the dominant factor that caused the students’ reticence in English classroom is individual factors that were the main indicator is underprepared with the percentage of 62.6%. The students felt nervous and did not confident to speak English. Therefore, it is better for the teacher to know the factors contribute to that reticence and could minimize the dominant factors in order to pursue the teaching and learning process more efficiently and enjoyable in learning English.